Economic and ecological transformation processes in East German water management regimes : the role of property rights and governance structures - Christian Schleyer (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2002)
Like in many low moor regions in East Germany, long-standing intensive arable farming - enabled by complex melioration - has caused soil deterioration and high water runoff in the 'Schraden'. More than ten years of economic and political transformation has worsened the situation and even added new problems. The visible consequences are drought periods in the summer, waterlogged plots in the spring and worn-down water management facilities that operate in an uncoordinated or even unauthorised way. It is here argued that the reallocation of property rights on melioration systems, together with ineffective co-ordination mechanisms, have impeded appropriate land use. Transformationrelated problems like the discontinuity of land property rights, the unclear legal situation regarding melioration plants built in socialist times, and highly-fragmented land ownership have not been effectively dealt with by the newly-established Water Association and Water Administration, respectively. Profoundly heterogeneous water-user interests and the complexity of ecosystem relations have contributed to the persistence of the problems. This analysis is based on regional planning material as well as on qualitative, semi-structured interviews with local stakeholders, representatives of the administration and politicians at all levels of government.
Keywords: 330; Bodenverbesserung; Eigentumsrecht; Landwirtschaft; Wasserwirtschaft; Neue Bundesländer